Interação do sistema calicreínas-cininas e fator de crescimento vascular endotelial (VEGF) em modelos de hipóxia intermitente: avaliação da angiogênese cardíaca nos animais selvagens e nocautes do receptor B2 de bradicinina - Visniauskas, Bruna [UNIFESP] (2016)
Low levels of oxygen in the tissues (hypoxia) occur in a number of pathophysiologic conditions such as the growth of tumors, heart disease and obstructive sleep apnea. During hypoxia, blood vessel growth (angiogenesis) is stimulated, leading to increased tissue O2 uptake. The vascular endothelial growth factor (VEGF) and the kallikrein-kinin system are essential for this process. As in humans, in intermittent hypoxia, an experimental model of obstructive sleep apnea, increased blood pressure, decreased cardiac output, left ventricular hypertrophy and pulmonary hypertension were described. However, the evidence of cardiac angiogenesis in this model are not clearly established. In order to investigate in vivo angiogenesis, left ventricular male mice C57BI6/J and knockouts for the bradykinin B2 receptor were subjected to intermittent hypoxia during 1, 2, 3, 4 or 5 months with subsequent histological evaluation of vascularization after the implantation of a Matrigel plug. The gene and protein expressions of vascular endothelial growth factor and components of the kallikrein-kinin system were also evaluated. A decrease in cardiac angiogenesis in vivo after 2, 3 and 4 weeks of intermittent hypoxia was found. Consistent with this data, although there is an increase in the expression of hypoxia induced factor since the first week, VEGF only increased after the third week (isoform 165) and the fourth week (isoform 121) and its VEGF-R2 receptor in the fifth week of intermittent hypoxia. None of these changes was observed in its B2 receptor knockout animals. In wild type animals, the B2 receptor had an increased expression since the first week of intermittent hypoxia that remained until the fifth week. Unexpectedly the gene expression of B1 receptor in wild type was decreased in the first week, while there was no change in protein expression. The expression of intracellular proteins (Akt and c-Src) had no change in left ventricular wild animals or knockouts. These results suggest that the intermittent hypoxia, unlike that seen in other models of hypoxia, the classic interaction of VEGF with the components of the kallikreinkinin system is not enough to stimulate the formation of new vessels. Additionally, the B2 receptor appears to be essential for the observed changes to occur in the model. Our results suggest a mechanism for the cardiac effects of obstructive sleep apnea.